Educational Social Intervention in the Resolution of Waqf Conflicts between Conflicting Parties - Widodo, Endro Dwi; Fauzan, Aris (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to describe the educational social intervention in resolving waqf conflicts among conflicting parties in Kotagede, Yogyakarta. The research employs a qualitative approach with a phenomenological design to explore the lived experiences and perceptions of the involved stakeholders. The data consist of primary information obtained through in-depth interviews, field observations, and documentation of legal and administrative records, while secondary data are derived from waqf-related legal literature and institutional archives. Data were analyzed using a phenomenological reduction process, which includes epoché, horizontalization, and thematic synthesis to interpret the essence of the conflict and its resolution. The findings reveal that social-educational interventions, particularly mediation and community deliberation facilitated by religious and local leaders, play a crucial role in achieving peace and maintaining waqf sustainability. The study concludes that successful conflict resolution requires not only legal mechanisms but also educational and participatory approaches that strengthen legal awareness, empower nadzir, and enhance community trust in waqf institutions.